Istikhdām al-Majāz al-Mursāl fi al-Balāghah al-‘Arābiyyah: Dirāsah fī Quwwat al-Ma’nā wa al-I’jāz al-Fannī fī al-Qur’ān [The Use of Metonymy in Arabic Rhetoric: A Study of the Strength of Meaning and the Artistic Miracle in the Qur’an] - Elmhemıt, Hüseyin; Taufiq, Muhammad (Center of Language Development, Institut Agama Islam Negeri Madura, 2024)
The uses of metonymy in Arabic rhetoric are very numerous. One of the purposes of using them is strength in meaning. Our saying: So-and-so is generous is less powerful in meaning than our saying: So-and-so has many ashes. Metaphors have been used a lot in the Holy Qur’an, and the use of body parts in metonymy was for many purposes in the Qur’an. These metaphors were chosen in a way that gives wonderful artistic implications consistent with the context in which the verses appear. In the research, metonymy was known, and some of its sections were discussed. Then, the research was divided according to the members. In which metonymies were used, and the use of those metonymies indicated a precise miracle, it is not possible for the truth or even any other metaphor to fulfill the intended meaning contained in the context of the verses. This research is an attempt to complete the efforts of the predecessors in showing the evidence of the endless Qur’anic miracle and its endless secrets.